KEY FACTORS DRIVING INDONESIA’S DIGITAL ECONOMY - Kharisma, Bayu; Rina Indiastuti; Mohamad Fahmi; Raden Muhammad Purnagunawan; Riki Relaksana; Muhammad Reyhan Akbar; Rafa Fayza Afrizal (Media Ekonomi, 2026)
This study aims to identify the key factors driving Indonesia’s digital economy. The research employs the Analytic Hierarchy Process (AHP) method, incorporating expert judgments from scholars and practitioners with in-depth knowledge of Indonesia’s digital economy. The research employs the Analytic Hierarchy Process (AHP) method, incorporating expert judgments from scholars and practitioners with in-depth knowledge of Indonesia’s digital economy. The findings indicate that digital governance and digital society are crucial factors to be prioritized for fostering regional digital economic growth. Furthermore, at the dimensional and indicator levels, human resources and digital skills are critical aspects that warrant greater emphasis to advance Indonesia’s digital economy. These findings underscore the importance of strengthening regulatory frameworks to support digital economic development, as well as enhancing efforts to build society’s skills and competencies to facilitate digital adoption.